Antihypertensive and antiproteinuric efficacy of ramiprilin children with chronic renal failure - Wühl, Elke; Mehls, Otto; Schaefer, Franz (Kidney international, 2004)
Antihypertensive and antiproteinuric efficacy of ramipril in children with chronic renal failure. - Background - While the antihypertensive and renoprotective potency of angiotensin-converting enzyme (ACE) inhibitors is well-established in adults with hypertension and/or chronic renal failure, little experience exists in pediatric chronic kidney disease.